![\qquad\qquad\huge\underline{{\sf Answer}}](https://tex.z-dn.net/?f=%5Cqquad%5Cqquad%5Chuge%5Cunderline%7B%7B%5Csf%20Answer%7D%7D)
Let's find the equivalent expressions ~
#1. PROBLEM
![\qquad \tt \dashrightarrow \:11x - 4x + 10x](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Cdashrightarrow%20%5C%3A11x%20-%204x%20%2B%2010x)
![\qquad \tt \dashrightarrow \:21x - 4x](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Cdashrightarrow%20%5C%3A21x%20-%204x)
![\qquad \tt \dashrightarrow \:17x](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Cdashrightarrow%20%5C%3A17x)
#2. PROBLEM
![\qquad \tt \dashrightarrow \:2(1 + 8y)](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Cdashrightarrow%20%5C%3A2%281%20%2B%208y%29)
![\qquad \tt \dashrightarrow \:(2 \times 1) + (2 \times 8y)](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Cdashrightarrow%20%5C%3A%282%20%5Ctimes%201%29%20%2B%20%282%20%5Ctimes%208y%29)
![\qquad \tt \dashrightarrow \:2 + 16y](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Cdashrightarrow%20%5C%3A2%20%2B%2016y)
Answer:
the solution is (2, -6)
Step-by-step explanation:
Substitute the second equation into the first, replacing y in the first:
2x - (-4x+2) = 10
Simplifying, we get:
2x + 4x - 2 = 10, or:
6x = 12, which yields x = 2.
Substituting 2 for x in the second equation yields y = -4(2) + 2 = 0, or y = -6
Then the solution is (2, -6).
Answer:
a. (x+5)^2 = 49
b. (x+7)^2 = (x+1)^2
Step-by-step explanation:
So the term "a number" is always going to be x. input x into the sentences. "X plus five, then squared, is forty-nine". when they do "is __", that means equal to. In the second question, seven more than x is x + 7 (the two numbers are interchangeable here). Equivalent also means equal. hope this helped :)
The probability of getting at most 2 tails is 7/8
Answer:
Alternate
Step-by-step explanation:
Because, as you can see, it is alternating